The Representation of Campbell's Monomyth in Mission: Impossible Dead Reckoning Part One (2023) Film - Helfina Devianti; Singgih Daru Kuncara (Fakultas Ilmu Budaya Universitas Mulawarman, 2026)
This study aimed to determine the representation of monomyth in the Mission: Impossible Dead Reckoning Part One film through the character Ethan Hunt using Campbell’s hero’s journey theory. This study also analyzed the plot and Ethan’s characterization to find out whether the plot in the modern film is related to Campbell’s hero’s journey theory. This study also focused on Ethan’s journey as the main character who goes through various events according to Campbell’s hero’s journey. The data source in this study is the Mission: Impossible Dead Reckoning Part One film. The story in this film was relevant to the modern world, exploring the dangers of out-of-control AI technology. The data taken in this study were dialogues, monologues, and events that represent the hero’s journey experienced by Ethan as the main character. The data collection technique was watching the film repeatedly, looking at the transcription of the film, highlighting important events, and taking notes for the analysis. This study used a structuralism approach that concentrates more on identifying and describing the structures in the hero’s journey. The analysis of this data showed that Mission: Impossible - Dead Reckoning Part One successfully represents the monomyth through the character of Ethan by using Campbell’s hero’s journey theory. The analysis of the plot and Ethan’s characterization in this film showed that although this film is modern, Campbell’s hero’s journey theory is still relevant and applicable, even though the story has a different context from traditional myths or legends.